2010
DOI: 10.1038/nnano.2010.64
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and manipulating the spin direction of individual atoms

Abstract: Single magnetic atoms on surfaces are the smallest conceivable units for two-dimensional magnetic data storage. Previous experiments on such systems have investigated magnetization curves, the many-body Kondo effect and magnetic excitations in quantum spin systems, but a stable magnetization has not yet been detected for an atom on a non-magnetic surface in the absence of a magnetic field. The spin direction of a single magnetic atom can be fixed by coupling it to an underlying magnetic substrate via the excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
150
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 140 publications
(173 citation statements)
references
References 18 publications
19
150
0
4
Order By: Relevance
“…During the past years, it has been demonstrated that the scanning tunnelling microscope (STM) is a powerful tool for building and controlling individual nanomagnetic structures, and has a great potential for use in the construction of future nanoscale magnetic devices. Previous studies of engineering individual magnetic atoms on surfaces [2] include exchange coupling between magnetic atoms [3][4][5][6], anisotropic spin environments of a single atom or dimer [7][8][9], and observations of Kondo effects [10,11]. Very recently, atom manipulation using the STM has been able to demonstrate important technological progress such as logic operations entirely based on engineered atomic spins [12] and dense nonvolatile storage of information by an atomicscale antiferromagnet [13].…”
Section: Introductionmentioning
confidence: 99%
“…During the past years, it has been demonstrated that the scanning tunnelling microscope (STM) is a powerful tool for building and controlling individual nanomagnetic structures, and has a great potential for use in the construction of future nanoscale magnetic devices. Previous studies of engineering individual magnetic atoms on surfaces [2] include exchange coupling between magnetic atoms [3][4][5][6], anisotropic spin environments of a single atom or dimer [7][8][9], and observations of Kondo effects [10,11]. Very recently, atom manipulation using the STM has been able to demonstrate important technological progress such as logic operations entirely based on engineered atomic spins [12] and dense nonvolatile storage of information by an atomicscale antiferromagnet [13].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] While covering both categories, our goal here is to present an overview of advancements in computing with spins and magnets from the macroscopic scale to the atomic scale. [16][17][18][19][20][21][22][23][24][25] …”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved by reducing the size of the information storage units going down to the nanoscale or even to single atoms [39]. Detecting and manipulating spins [40] with high accuracy on the atomic scale is essential for future technological applications.…”
Section: Introductionmentioning
confidence: 99%